Enabling the complete valorization of hybrid Pennisetum: Directly using alkaline black liquor for preparing UV-shielding biodegradable films - Qian, Haojiang; Fan, Yafeng; Chen, Jiazhao; He, Linsong; Sun, Yongming; Li, Lianhua (Frontiers in Bioengineering and Biotechnology, 2022)
The conversion of lignocellulosic biomass into various high-value chemicals has been a rapid expanding research topic in industry and agriculture. Among them, alkaline removal and utilization of lignin are important for the accelerated degradation of biomass. Modern biorefinery has been focusing the vision on the advancement of economical, green, and environmentally friendly processes. Therefore, it is indispensable to develop cost-effective and simple biomass conversion technologies to obtain high-value products. In this study, the black liquor (BL) obtained from the alkaline pretreatment of biomass was added to polyvinyl alcohol (PVA) solution and used to prepare degradable ultraviolet (UV) shielding films, achieving direct and efficient utilization of the aqueous phase from alkaline pretreatment. This method avoids the extraction step of lignin fraction from black liquor, which can be directly utilized as the raw materials of films preparation. In addition, the direct use of alkaline BL results in films with similar UV-shielding properties, higher physical strength, and similar thermal stability compared with films made by commercial alkaline lignin. Therefore, this strategy is proposed for alkaline-pretreated biorefineries as a simple way to convert waste BL into valuable products and partially recover unconsumed sodium hydroxide to achieve as much integration of biomass and near zero-waste biorefineries as possible.